Ruta fluvial y el turismo recreativo en el Puerto Bolívar de Machala - López Hidalgo, Lider Reynel (2019)
The following case study was carried out in the city of Machala Province of El Oro, known for its natural attractions being the most outstanding the Puerto Bolívar and the Island Jambelí, oriented to Tourism as a factor of socioeconomic development and cultural conservation of the rural areas for a contribution to the economy of the inhabitants of the canton Machala providing them to enjoy their natural attractions. Although there is a river route that covers from Puerto Bolívar to Jambelí Island, this is very little visited by tourists due to the lack of planning to promote it by tourism, which prevents the tourist development of the canton. This paper aims to solve the study problem, as is the need to develop a recreational tourism on the Puerto Bolívar river route towards Jambelí Island for the improvement of the quality of life of the owners of the boats engaged in this activity, through the media preparation of work and mental, to satisfy the basic needs of the tourist.